The distribution of TP53 gene polymorphisms in chronic lymphocytic leukemia patients, sufferers of chornobyl nuclear power plant accident - Bilous, N.I.; Abramenko, I.V.; Chumak, A.A.; Dyagil, I.S.; Martina, Z.M. (Experimental Oncology, 2016)
Previous analyses in a cohort of Chornobyl cleanup workers revealed significantly increased radiation-related risk for all leukemia types, including chronic lymphocytic leukemia (CLL). Numerous investigations emphasized the significance of genetic susceptibility to the radiation carcinogenesis. The aim of the work was to study the distribution of TP53 single nucleotide polymorphisms (SNPs) in CLL patients exposed to ionizing radiation (IR) due to Chornobyl nuclear power plant accident and estimate their impact on disease development. Materials and Methods: The TP53 exonic and intronic SNPs were analyzed in 236 CLL patients by polymerase chain reaction and direct sequencing. The main group included 106 IR exposed CLL patients and the control group was composed of 130 IR non-exposed CLL patients. Results: Nineteen TP53 SNPs were found in the observed CLL cohort. No significant differences were found between the main and the control groups, but increased frequencies of T/T rs12947788 + G/G rs12951053 homozygotes and rs146340390 C/T variants were found among IR-exposed CLL patients compared with healthy Europeans (data from the 1000 Genomes Project). Rare nucleotide substitution rs146340390 (c.665C>T) was found only in the main group. These features were primarily typical for the most affected group of IR-exposed patients, namely, cleanup workers engaged in emergency works in the 2nd quarter of 1986. Conclusion: These preliminary findings don’t contradict the assumption on possible influence of IR on CLL development via the p53-dependent pathway. This article is a part of a Special Issue entitled “The Chornobyl Nuclear Accident: Thirty Years After”.